752 Evaluating the Use of Immersive Virtual Reality Simulation in Orthopaedic Trauma Cases; A Construct Reality Study. (4th May 2021) - Feeley, A; Sheehan, E; Merghani, K
Abstract: Introduction: Changing surgical training models as a result of reduced working hours, shorter schemes and the recent pandemic has resulted in reduced operative hours being logged by trainees. Novel and validated training methods are needed to rectify the deficit faced by surgical trainees, to maintain continued development and retention of skill throughout their training scheme. Method: A comparative interventional study was carried out in a regional trauma unit hospital. Volunteers were stratified into novice, intermediate and expert groups based on self-reported levels of experience. Each carried out a simulated proximal femoral nail on a virtual platform following instruction on its use. Face and content validity was also assessed. Results: The proximal femoral nail module demonstrated construct validity. Intermediate surgeons performed significantly better than novices (P=.03), with shorter procedural times (P=.013) Three of the intermediate group achieved the proficiency level set by the expert group. Time taken to completion for expert surgeons was less than intermediate group, although this did not reach significance (P=.16). Face and content validity was reported for the module. Conclusions: The proximal femoral nail module on the Precision OS platform demonstrated good face, content, and construct validity under expert scrutiny. Further research evaluating use of virtual platforms to optimise surgical training is needed.